A late Wisconsin (32–10k cal a BP) history of pluvials, droughts and vegetation in the Pacific south‐west United States (Lake Elsinore, CA). (5th February 2018) - Kirby, M. E.; Heusser, L.; Scholz, C.; Ramezan, R.; Anderson, M. A.; Markle, B.; Rhodes, E.; Glover, K. C.; Fantozzi, J.; Hiner, C.; Price, B.; Rangel, H.
ABSTRACT: Continuous, sub‐centennially resolved, paleo terrestrial records are rare from arid environments such as the Pacific south‐west United States. Here, we present a multi‐decadal to centennial resolution sediment core (Lake Elsinore, CA) to reconstruct late Wisconsin pluvials, droughts and vegetation. In general, the late Wisconsin is characterized by a wetter and colder climate than during the Holocene. Specifically, conditions between 32.3 and 24.9k cal a BP are characterized by large‐amplitude hydrologic and ecologic variability. Highlighting this period is a ∼2000‐year glacial mega‐drought (27.6–25.7k cal a BP) during which the lake shallowed (3.2–4.5 m depth). This period is approximately coeval with a Lake Manix regression and an increase in xeric vegetation in the San Bernardino Mountains (Baldwin Lake). The Local Last Glacial Maximum (LLGM) is bracketed between 23.3 and 19.7k cal a BP − a ∼3000‐year interval characterized by reduced run‐off (relative to the glacial), colder conditions and vegetative stability. Maximum sustained wetness follows the LLGM, beginning at 19.7 and peaking by 14.4k cal a BP. A two‐step decrease in runoff characterizes the Lateglacial to Holocene transition; however, the vegetation change is more complex, particularly at the beginning of the Younger Dryas chronozone. By 12.6–12.4k cal a BP, the climate achieved near Holocene conditions.